Analysis of health workforce preparedness in enhancing community resilience to flood disasters: A literature review - Novrikasari Novrikasari; Febri Adriati; Akma Listiana; Riyanti Riyanti; Risa Mundari; Muhlisin Muhlisin (Lentera Perawat, 2026)
Background: Floods are one of the most common hydrometeorological disasters in Indonesia and have a significant impact on public health. In this context, the preparedness of healthcare workers is a key factor in strengthening community resilience in the face of disaster situations. This study aims to analyze the preparedness of healthcare workers in enhancing community resilience to floods through a literature review approach. Methods: A systematic literature search was conducted using the PubMed, ScienceDirect, and Google Scholar databases covering the years 2020–2025. A total of 864 articles were identified in the initial stage. After removing duplicates and screening based on titles and abstracts, 69 articles were selected that met the criteria for further review in the full-text stage. Next, 15 articles were selected based on the inclusion criteria, namely: studies focusing on the preparedness of health workers in the context of disasters, related to floods or hydrometeorological disasters, original research articles, and available in full text in Indonesian or English. Results: The study results were synthesized thematically, yielding four main themes: individual preparedness of healthcare workers, encompassing knowledge, attitudes, and skills; support from healthcare facilities and systems, including infrastructure and resource readiness; cross-sectoral coordination in disaster management; and community education focused on strengthening resilience. These four themes contribute to enhancing the community’s adaptive capacity, accelerating emergency response, and reducing post-disaster health impacts. Conclusion: In conclusion, strengthening healthcare workers’ preparedness through continuous training, disaster simulations, and integrated policy support is essential for enhancing community resilience against flood disasters.